PENGEMBANGAN MEDIA KOMIK PADA MATERI KEANEKARAGAMAN HAYATI BAGI SISWA KELAS X SMA - Ana Mandasari; Mariani Natalina L; Nursal Nursal (Biogenesis, 2021)
This study aims to produce comic media on biodiversity lesson for class X senior high school students. This research was conducted at the Faculty of Teacher Training and Education Riau University, Public Senior High School 8 Pekanbaru and Public Senior High School 6 Pekanbaru in November-February 2021. The type of research used is Research and Development (R&D) with the ADDIE research model consisting of 5 stages, namely analysis, design, development, implementation and evaluation. In this research, it is limited only to the development stage. Data collection instruments in the form of validation sheets and questionnaires of respondents. The results of the validation of comics media on biodiversity lesson for students of class X senior high school are at an average value of 3,60 with a very valid category. The result of the limited test score are 3,42 with a very good category. Thus, comics on biodiversity material for students of class X of senior high school have been successfully developed with very good quality and can be implemented on a wider scale.